FOSTERING AND EMPOWERING DIGITAL BAZNAS - Fandi Kurniawan (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
In an era of increasingly rapid technology, its impact has been felt in various circles, including in the management of zakat. This information system aims to facilitate data management, starting from entering information about zakat payers and recipients, calculating zakat calculations to making zakat fund reports at the Palembang City Baznas. Previously, the Palembang City Baznas only used simple computer calculations using Microsoft Excel and Word. Because of that, an information system is needed that can regulate the management process in managing zakat. The method used is direct analysis to BAZNAS locations and design of interfaces, rules, and design thinking. This research produced a hybrid-based BAZNAS Information System for Palembang City. This system is expected to increase efficiency and accuracy in processing zakat data and facilitate the process of making reports for the Palembang City Baznas